Direct and Indirect Effects of Accessibility: Infrastructure and Regional Access - Ildikó Győrffy (Theory, Methodology, Practice, 2011)
Nowadays the topic of accessibility is becoming more and more popular as a national and international research field of study. Regarding its aim, the main question is about the connection between the adequate accessibility and development tendencies (Tóth 2007; Tagai 2007; Dusek and Szalkai 2007; Watanabe 1995). Accessibility as well as the infrastructure is defined in different ways according to the different approaches in the economic literature. Generally it is declared that the location of a place is inadequate if it is not easily accessible. According to Nemes Nagy (2007) the opposite statement can also occur: e.g., from a military or defence point of view, tough accessibility can be a positive term; in the case of tourism it can be also an attraction, appreciating the “resort value” of a territory. Tóth (2006) cites Keeble with the definition of accessibility (as the main product of transportation); regarding Keeble, the peripherality is synonymous with the relative accessibility (or lack) of the economic activity. Problems arise in the case of these territories, because the accessibility terms do not increase with the extension of infrastructure, namely the large investments take place where the demand arises, so the benefiting places are mostly the centre or core areas. Accessibility and its “tool”, infrastructural extension, can be measured in several ways, as I discussed in my earlier research work (Győrffy 2010). During the examination of accessibility, we consider roles and spatial movements, and the targets are usually the capital city, the regional centre, the county capitals and the motorway junctions (Bajmócy and Kiss 1999; Edelényi 2004; Kocziszky 2004; Nemes Nagy 2009). In this paper, I analyse the accessibility of all the Hungarian subregions, taking the time and distance connections in a 174*173 matrix. Further on I analysed the relationship between the development data and accessibility indicators particularly in terms of centre-periphery relations. I tried to find out that improvement of the road infrastructure through the better accessibility what kind of spillover accompanies, how it effects on the social-economical position of a region, or can we talk about direct effect at all?